The Influence of E-HRM Implementation on Human Resource Behaviori in Indonesia in The Era Of Industry 4.0 and Society 5.0 - Ainun Faridah; Khuzaini Khuzaini; Syahrial Shaddiq; Dwi Sogi Sri Redjeki; Fanlia Prima Jaya; Yuniana Cahyaningrum; Kamsariaty Kamsariaty; Herlina Lusiana; Sulastini Sulastini (Hut Publication Business and Management, 2023)
Human resource management (HRM) is an important function in an organization to achieve its goals. In recent years, developments in information and communications technology (ICT) have brought about major changes in the way HRM is implemented. One of the innovations in HRM is the application of E-HRM (electronic human resource management). E-HRM is the use of ICT to support HRM functions. Implementing E-HRM can provide various benefits for organizations, such as increasing efficiency and effectiveness, increasing the quality of information, and increasing employee satisfaction. This research aims to examine the influence of implementing E-HRM on human resource behavior in Indonesia. This research uses a survey method with employee respondents from various companies in Indonesia. The research results show that the application of E-HRM has a positive influence on human resource behavior, namely: (1) increasing employee commitment, (2) increasing employee job satisfaction and (3) increasing employee performance